The nation-state factor in global news reporting: A study of the BBC World News and Al Jazeera English coverage - Mohd Faizal Kasmani (Sage Publications Inc, 2024)
This article aims to understand to what extent the nation-state context explained the coverage of the BBC World News and Al Jazeera English during the 2009 Iranian election. It mainly examines how the leaders of the Iranian political factions, namely, Mahmoud Ahmadinejad and Mir Hossein Mousavi were represented by the BBC World News and Al Jazeera English. This study triangulates textual analysis of the BBC World News and Al Jazeera English news, with the results of interviews with BBC World News reporters and editors who were involved in the coverage of the election. The analysis found that there were differences in the portrayal of the BBC World News and Al Jazeera English. It concludes that Al Jazeera English's all-Iranian correspondents have a closer dependence on their country of origin than their host nation-state, while the national affiliation appeared to significantly explain the reporting of the BBC World News.